Innovation, coopetition and spillover effects in European regions - Popescu, Irina Alina; Reis Mourao, Paulo; Bilan, Yuriy (Journal of Business Economics and Management, 2023)
Innovation and investment are critical to economic growth. In this article, we address the complex task of evaluating the capacity of regional innovation to increase investment and generate spillovers in regions of the European Union (EU) from both spatial and temporal perspectives. Using panel data estimation methods and exploring the effects of dynamic spatial autocorrelation, our findings show a positive spatial autocorrelation at the level of EU regions. We also observed spatial competition, both in terms of the distribution of investments and in terms of the diffusion of short-term innovation gains. We argue that, in the short term, EU regions tend to behave as competitors for investment fixing, but in the long run, innovation has the potential to generate spillover effects on neighbouring regions. Furthermore, we find that investment patterns were characterized by a significant temporal autocorrelation, showing that shocks to investment in regions tend to be absorbed in a few periods. This paper attempts to fill existing gaps by using estimation methods for dynamic spatial panel data to identify and explore the effects of regional innovation on investment for the 154 European Union regions, and reports original findings as regards the knowledge spillover across European regions.